Rings which have (m,n)-flat injective modules - Zhanmin, Z.; Zhangsheng, X. (Algebra and Discrete Mathematics, 2005)
A ring R is said to be a left IF − (m, n) ring if
every injective left R-module is (m, n)-flat. In this paper, several
characterizations of left IF − (m, n) rings are investigated, some
conditions under which R is left IF−(m, n) are given. Furthermore,
conditions under which a left IF −1 ring (i.e., IF −(1, 1) ring) is a
field, a regular ring and a semisimple ring are studied respectively.